(untitled) (Ciudades, 2025)
In the last two decades, the immigrant population of foreign origin has increased in Spanish cities. The metropolitan area of Las Palmas de Gran Canaria (Large Urban Area) is a clear example in an insular and ultraperipheral context. This article analyses the levels of segregation and the location patterns of the foreign-origin population in this area over time in order to establish a location model based on the spatial analysis of bivariate correlations with income. A statistically significant model is established and the role played by this population in relation to the real estate network is indicated.